Transformation of Islamic education values "MAJA LABO DAHU" through parents in Bima - Hermawansyah, Hermawansyah; Naro, Wahyuddin; Muzakkir, Muzakkir; Syamsuddin, Syamsuddin (Edelweiss Applied Science and Technology, 2025)
Rapid changes in values and norms often expose children to negative influences, such as deviant behavior, consumerism, and a lack of social awareness. In this context, the role of parents as the first and main educators becomes crucial. Therefore, this study aims to examine the transformation of "Maja Labo Dahu" ethics education through parents in Bima. With a qualitative approach, this research allows all information to be studied in depth to draw the right conclusions. The results show that the transformation of Islamic education values of Maja Labo Dahu through parents in Bima has a significant positive impact on the formation of character and behavior of the younger generation.